2004
DOI: 10.1073/pnas.0308626100
|View full text |Cite
|
Sign up to set email alerts
|

Postsynaptic N -methyl- d -aspartate receptor function requires α-neurexins

Abstract: ␣-Neurexins are neuron-specific cell-surface molecules that are essential for the functional organization of presynaptic Ca 2؉ channels and release sites. We have now examined postsynaptic glutamate receptor function in ␣-neurexin knockout (KO) mice by using whole-cell recordings in cultured neocortical slices. Unexpectedly, we find that ␣-neurexins are required for normal activity of N-methyl-D-aspartate (NMDA)-but not ␣-amino-3-hydroxy-5-methyl-4-isoxyzolepropionic acid (AMPA)-type glutamate receptors. In ␣-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
2
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(95 citation statements)
references
References 33 publications
7
84
2
1
Order By: Relevance
“…In support of this overall concept, ␣-neurexin triple KO mice exhibit major impairments in synaptic transmission that manifest largely, but not exclusively, as presynaptic changes (9)(10)(11)(12)(13). Importantly, ␣-neurexin KO mice do not display a major decrease in the number of excitatory synapses, and only a moderate decrease in inhibitory synapses (9,13).…”
mentioning
confidence: 59%
“…In support of this overall concept, ␣-neurexin triple KO mice exhibit major impairments in synaptic transmission that manifest largely, but not exclusively, as presynaptic changes (9)(10)(11)(12)(13). Importantly, ␣-neurexin KO mice do not display a major decrease in the number of excitatory synapses, and only a moderate decrease in inhibitory synapses (9,13).…”
mentioning
confidence: 59%
“…In fact, we reported previously that the GABA B R-mediated modulation of Ca V 2.2 channels, required for its effect on vesicle release (58), was also impaired at excitatory brainstem synapses of α-Nrxn KO mice (45). Even more importantly, α-Nrxn is abundantly expressed in glutamatergic neurons as well (12) and has unequivocal effects on release from excitatory synapses (9,44,46,78). These results cannot be explained by a simple association of α-Nrxn with inhibitory and, of β-Nrxn with excitatory terminals as cautioned before (37).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research has identified several molecules, mostly ion channels and receptors, which are functionally impaired when Nrxn expression is altered. Nrxn variants have been found to affect voltage-dependent calcium channels (9,10), GABA A R (7, 37), NMDAR (44), GABA B R (36,45), nicotinergic acetylcholine receptors (69), and AMPAR (47). These ionotropic and metabotropic receptors represent "target molecules" of Nrxn that may include some physical association, but it appears unlikely that the functional link to all these requires stable protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of the -form of all three Nrxns in mice impairs presynaptic neurotransmitter release, and postsynaptic receptor function [81][82][83]. KO of Nlgn-1, -2, and -3 in mice causes neonatal lethality, as well as massive synaptic alterations [80].…”
Section: Neurexins and Neuroliginsmentioning
confidence: 99%